Proteolytic activity and degradation of bovine versus human dentin matrices - Inagati, Cristiane Mayumi [UNESP]; Scheffel, Débora Lopes Salles; Anovazzi, Giovana [UNESP]; Alonso, Juliana Rosa Luiz [UNESP]; Christoffoli, Marcelly Tupan; Pashley, David Henry; De Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (FapUNIFESP (SciELO), 2021)
Non-human teeth have been commonly used in research as replacements for human teeth, and potential dissimilarities between the dental tissues should be considered when interpreting the outcomes. Objective: To compare the proteolytic activity and degradation rate of bovine and human dentin matrices. Methodology: Dentin beam specimens were obtained from human molars (n=30) and bovine incisors (n=30). The beams were weighed hydrated and after complete dehydration to obtain the mineralized wet and dry masses. Then, the beams were demineralized in 10 wt% phosphoric acid. Next, 15 beams from each substrate were randomly selected and again dehydrated and weighed to obtain the initial demineralized dry mass (DM). Then, the beams were stored in saliva-like buffer solution (SLBS) for 7, 14 and 21 days. SLBS was used to evaluate hydroxyproline (HYP) release after each storage period. The remaining beams of each substrate (n=15) were tested for initial MMP activity using a colorimetric assay and then also stored in SLBS. DM and MMP activity were reassessed after 7, 14 and 21 days of incubation. The data were subjected to two-way ANOVA tests with repeated measures complemented by Bonferroni’s tests. Unpaired two-tailed t-tests were also used (p<0.05). Results: Similar water and inorganic fractions were found in human and bovine dentin, while human dentin had a higher protein content. The most intense proteolytic activity and matrix deterioration occurred short after dentin was demineralized. Both substrates exhibited a sharp reduction in MMP activity after seven days of incubation. Although human dentin had higher MMP activity levels, greater HYP release and DM loss after seven days than bovine dentin, after 14 and 21 days, the outcomes were not statistically different. Conclusion: Bovine dentin is a suitable substrate for long-term studies involving the degradation of dentin matrices.
Keywords: Animals; Collagen; Dentin; Hydroxyproline; Matrix metalloproteinases